(untitled) (gjstudies, 2026)
This research investigates the transformative potential of integrating big dataanalytics into financial reporting processes, proposing a novel methodological framework that diverges from conventional approaches. While existing literature predominantly focuses on isolated applications of analytics in auditing or fraud detection, this study introduces a holistic, process-oriented model that embeds analytics throughout the entire financial reporting lifecycle—from transaction captureto disclosure. The originality of this work lies in its conceptualization of financialreporting not as a static, periodic output but as a dynamic, data-intensive processthat can be continuously optimized for accuracy, timeliness, and predictive insight.We formulate and address three primary research questions: (1) How can big dataanalytics be structurally integrated into each phase of the financial reporting process to enhance reliability and efficiency? (2) What are the critical technical andorganizational prerequisites for successful integration? (3) What novel forms ofassurance and stakeholder value can such integration generate beyond traditionalfinancial statements? Our methodology employs a hybrid design-science and casestudy approach, developing a reference architecture and validating its componentsthrough simulated application to complex, multi-source financial data scenarios.The results demonstrate that integrated analytics can significantly reduce manualreconciliation efforts, enable real-time anomaly detection, and facilitate the generation of forward-looking, non-financial performance indicators. Furthermore, thestudy reveals a paradigm shift towards ’continuous reporting,’ where the boundarybetween operational data and reported information becomes increasingly blurred.The conclusion articulates the original contribution of this research: a comprehensive, actionable framework for the data-driven re-engineering of financial reporting,challenging the prevailing compliance-centric model and proposing a new valuecreation oriented paradigm. This work provides a foundational roadmap for practitioners and opens several novel avenues for academic inquiry at the intersectionof accounting, data science, and information systems.